Effects of PWHT on the microstructure, corrosion, tribology, and mechanical properties of mild steel welds under different joining positions: Experimental and Numerical Study - Behrouz Bagheri Vanani; Mohammad Reza Mehraban Dehaqani; Mahmoud Abbasi; Mahdi Sadeqi Bajestani; Melika Mohammadkhah; Sandra Klinge (Journal of Materials Research and Technology)
St37 mild steel has a broad range of applications in industry. The weldability of St37 using the Gas Metal Arc Welding (GMAW) method was investigated under flat and vertical-up welding positions. The effects of post-weld heat treatment (PWHT) on the microstructure, mechanical properties, corrosion resistance, and tribological behavior of the welded samples were thoroughly examined. A thermo-metallurgical finite element model (FEM) was employed to analyze the thermal history, phase distribution, and residual stress variation in double-sided butt-welded ST-37 samples during the GMAW process. The results indicated that PWHT significantly enhanced phase uniformity and microstructural homogeneity in the weld zone, leading to improved mechanical performance. Metallurgical defects, such as porosities, were effectively eliminated after PWHT, and residual stresses in the joint were significantly reduced. Corrosion resistance, influenced by microstructural evolution, followed the trend: Base metal ≥ Flat weld + PWHT > Flat weld > Vertical weld + PWHT > Vertical. Moreover, PWHT improved the wear resistance of welded specimens. This enhancement was attributed to stress relaxation, carbide formation through precipitation hardening, and the reduction of metallurgical defects. Notably, PWHT also contributed to a shift in the dominant wear mechanism from adhesive to abrasive in both flat and vertical welds.